2020
DOI: 10.3390/polym12102371
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetorheological Effect of Magnetoactive Elastomer with a Permalloy Filler

Abstract: Within the frames of this study, the synthesis of a permalloy to be used as a filler for magnetoactive and magnetorheological elastomers (MAEs and MREs) was carried out. By means of the mechanochemical method, an alloy with the composition 75 wt.% of Fe and 25 wt.% of Ni was obtained. The powder of the product was utilized in the synthesis of MAEs. Study of the magnetorheological (MR) properties of the elastomer showed that in a ~400 mT magnetic field the shear modulus of the MAE increased by a factor of ~200,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…These results agree qualitatively with the previous predictions where the coarse grained network model is used [ 59 ]. In recent work, the MR effect has been studied by considering the local particle rearrangement during the shear deformation, and significant MR effects have been reported [ 60 ]. In contrast, in this work, we explicitly consider the effect of the macroscopic shape of the MAE, assuming the particle distribution remains isotropic even after the deformation.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree qualitatively with the previous predictions where the coarse grained network model is used [ 59 ]. In recent work, the MR effect has been studied by considering the local particle rearrangement during the shear deformation, and significant MR effects have been reported [ 60 ]. In contrast, in this work, we explicitly consider the effect of the macroscopic shape of the MAE, assuming the particle distribution remains isotropic even after the deformation.…”
Section: Discussionmentioning
confidence: 99%
“…44 Due to the difficulty of preventing this aggregation effects, it can be concluded that using superparamagnetic NPs could present significant advantages when it comes to improve the performance of these composites, as it was demonstrated by Meharthaj et al 41 As for the irregular shape of the particles, the TEM images show that only the Permalloy and Ni nanoparticles are characterized by almost perfect spherical shapes, while the others NP are much more irregular. It has been pointed out 45 that the irregular shape of the particles can cause a significant internal friction that increases the loss modulus of the composite (which is positive for damping applications), but also may affect the durability of the material. Most studies have focused on the effect of the particle shape on the sedimentation of MR fluids, 46 although it has been concluded that for fields where the particles reach saturation, little difference exists in the MR effect with particles of different shapes.…”
Section: Magnetorheological Propertiesmentioning
confidence: 99%
“…The mechanical properties of MAEs are highly sensitive to the initial shape of a sample [35][36][37][38] as well as to the particle microstructure [39][40][41]. MAEs possess the ability to change their elastic moduli in the presence of an external magnetic field [42][43][44][45]. To observe large enhancements in the moduli, one needs a very soft polymer matrix.…”
Section: Introductionmentioning
confidence: 99%